Genome‐Wide Study Links PNPLA3 Variant With Elevated Hepatic Transaminase After Acute Lymphoblastic Leukemia Therapy. Issue 1 (4th April 2017) - Liu, Y; Fernandez, CA; Smith, C; Yang, W; Cheng, C; Panetta, JC; Kornegay, N; Liu, C; Ramsey, LB; Karol, SE; Janke, LJ; Larsen, EC; et al.
Abstract : Remission induction therapy for acute lymphoblastic leukemia (ALL) includes medications that may cause hepatotoxicity, including asparaginase. We used a genome‐wide association study to identify loci associated with elevated alanine transaminase (ALT) levels after induction therapy in children with ALL enrolled on St. Jude Children's Research Hospital (SJCRH) protocols. Germline DNA was genotyped using arrays and exome sequencing. Adjusting for age, body mass index, ancestry, asparaginase preparation, and dosage, the PNPLA3 rs738409 (C>G) I148M variant, previously associated with fatty liver disease risk, had the strongest genetic association with ALT ( P = 2.5 × 10 ‐8 ). The PNPLA3 rs738409 variant explained 3.8% of the variability in ALT, and partly explained race‐related differences in ALT. The PNPLA3 rs738409 association was replicated in an independent cohort of 2, 285 patients treated on Children's Oncology Group protocol AALL0232 ( P = 0.024). This is an example of a pharmacogenetic variant overlapping with a disease risk variant.